Asymmetric Henry reaction of trifluoromethyl ketone and aldehyde using Cu(II)-complex: computational study offers the origin of enantioselectivity with varied size of catalysts. Issue 33 (19th August 2015) - Das, Anjan; Choudhary, Manoj K.; Kureshy, Rukhsana I.; Jana, Kalyanashis; Verma, Shailesh; Khan, Noor-ul H.; Abdi, Sayed H.R.; Bajaj, Hari C.; Ganguly, Bishwajit
Abstract: Chiral ligand3 was synthesised from inexpensive and readily available (1 R, 2 R )-(+)-1, 2-diphenyl-1, 2-diaminoethane and tert -butylbromoacetate. In situ generated complex obtained by the reaction of ligand3 with copper triflate was used as catalyst for asymmetric Henry reaction of trifluoromethyl ketone having different substituents in the aromatic ring with nitromethane at 0 °C in presence of N, N -DIPEA as additive to give nitroaldol products in excellent enantioselectivity ( ee upto 99%) with good yield (upto 80%). Ligand3 with in situ generated complex with copper acetate was also found to be good catalyst for asymmetric nitroaldol reaction of aldehydes ( ee up to 80–92%, yield up to 85%) with nitromethane at −5 °C. The DFT calculations performed with B3LYP and M06-2X functionals revealed the role of non-covalent interactions (such as π–π interaction and hydrogen bonding) and the steric factors in the catalyst play important role towards the enhancement of enantioselectivity. Graphical abstract: